A Sneak peek (1970-2021) Into Phytochemistry and Ethnomedical Properties of Solanum Nigrum Linn (Makoi) (Journal of Pharmaceutical Negative Results, 2022)
Introduction: Plants have always played a substantial role in the traditional medicine system worldwide. In India and other parts of theworld, Solanum Nigrum Linn. is one of the most promising and reliable sources of medicine in the traditional medicine system. It iswell known for its dynamic therapeutic properties. The concrete objective of selecting this plant is to consolidate its bioactive elementsand possibly medicinal qualities. So that future scientists and researchers may progress novel pharmaceuticals for pre-clinical andclinical trials, which could be launched as new targeted therapeutic options.Method: This review summarized the previous three decades' worth of scientific publications from online databases such as GoogleScholar, PubMed, ScienceDirect, Web of Science, and library books to assemble their possible phytopharmacological and therapeuticpotentials.Results: From the ongoing research database, S. Nigrum possesses a plethora of active phytoconstituents like glycoproteins,polysaccharides, polyphenolic compounds, and glycoalkaloids which are responsible for various pharmacological activities such asantioxidant, anticancer, antitumor, hepatoprotective, antidiabetic, and anti-asthmatic etc.Conclusion: This mystic herb has exhibited numerous ethnomedical properties in humans. Our research findings provide clear evidencethat S. Nigrum could be a potential natural source of several ailments and might be marketed as an alternative to contemporarymedicines. The stem, flower, root, and seed contain numerous dynamic bioactive constituents that are unexplored. Future researchershave an excellent opportunity to investigate them and elucidate their biomedical scientific activities and mechanisms in differentdiseases.